Using Targeted Sequencing of Paralogous Sequences for Noninvasive Detection of Selected Fetal Aneuploidies. (6th January 2020) - Ellison, Christopher K; Sun, Youting; Hogg, Grant; Fox, Jesse; Tao, Helen; McCarthy, Erin; Sagoe, Bright; Azab, Mostafa A; Mazloom, Amin R; Tynan, John; Burcham, Timothy; Kim, Sung K; et al.
Abstract: BACKGROUND: Current methods for noninvasive prenatal testing (NIPT) ascertain fetal aneuploidies using either direct counting measures of DNA fragments from specific genomic regions or relative measures of single nucleotide polymorphism frequencies. Alternatively, the ratios of paralogous sequence pairs were predicted to reflect fetal aneuploidy. We developed a NIPT assay that uses paralog sequences to enable noninvasive detection of fetal trisomy 21 (T21) and trisomy 18 (T18) using cell-free DNA (cfDNA) from maternal plasma. METHODS: A total of 1060 primer pairs were designed to determine fetal aneuploidy status, fetal sex, and fetal fraction. Each library was prepared from cfDNA by coamplifying all 1060 target pairs together in a single reaction well. Products were measured using massively parallel sequencing and deviations from expected paralog ratios were determined based on the read depth from each paralog. RESULTS: We evaluated this assay in a blinded set of 480 cfDNA samples with fetal aneuploidy status determined by the MaterniT21 ® PLUS assay. Samples were sequenced (mean = 2.3 million reads) with 432 samples returning a result. Using the MaterniT21 PLUS assay for paired plasma aliquots from the same individuals as a reference, all 385 euploid samples, all 31 T21 samples, and 14 of 16 T18 samples were detected with no false positive results observed. CONCLUSIONS: This study introduces a novel NIPT aneuploidy detection approach using targeted sequencing of paralog motifs and establishes proof-of-concept for a potentially low-cost, highly scalable method for the identification of selected fetal aneuploidies with performance and nonreportable rate similar to other published methods.